Better in-hospital outcome among hypertensive subjects developing acute myocardial infarction-study in a tertiary cardiac care center in Bangladesh (Bangladesh Heart Journal, 2016)
Background:In-hospital complications and mortality in hypertensives developing acute myocardial infarction(AMI) may be different from those of normotensive counterpart.The aim of the current study was to analyze in-hospital complication and outcome of AMI in hypertensive patients and compare it with age and sex matched normotensive AMI patients.Methods: In-hospital complications of 112 hypertensive patients with AMI admitted over a period of 1 year (April 2014 to March 2015) were compared with the control group. Location and types of AMI were determined by ECG. Patients were considered to be hypertensive if they were taking antihypertensive treatment or were found to have a systolic blood pressure (SBP) e140 mmHg and/or a diastolic blood pressure (DBP) e90 mmHg on repeated measurements. Both groups were studied prospectively. The results were analyzed by SPSS software.Results:Out of total 112 patients 69 were male and 43 were female in each group. Male: female ratio was 1.6:1. Mean age of the study population was 67.3±10.2 yrs (range 41 to 83 yrs). Mean blood pressure values were 145.7±11.5/88.3±8.9 mmHg in the hypertensive and 127.3±9.7/75.8±5.6 mmHg in normotensive group respectively. A significantly higher prevalence of diabetes, dyslipidemia, chronic kidney disease, stroke and peripheral vascular disease were found in the hypertensive compared with the normotensive subjects. Hypertensive AMI patients had higher left ventricular ejection fraction compared with the normotensives(0.51±0.13 vs 0.47±0.15). A higher frequency of paroxysmal atrial fibrillation(AF) (10.7% vs 7.1%, P